IP mobility management for vehicular communication networks: challenges and solutions (2011)
Vehicular communication networks have emerged as a promising platform for the deployment of safety and infotainment applications. The stack of protocols for vehicular networks will potentially include Network Mobility Basic Support (NEMO BS) to enable IP mobility for infotainment and Internet-based applications. However, the protocol has performance limitations in highly dynamic scenarios, and several route optimization mechanisms have been proposed to overcome these limitations. This article addresses the problem of IP mobility and its specific requirements in vehicular scenarios. A qualitative comparison among the existent IP mobility solutions that optimize NEMO BS in vehicular networks is provided. Their improvements with respect to the current standard, their weaknesses, and their fulfillment of the specific requirements are also identified. In addition, the article describes some of the open research challenges related to IP mobility in vehicular scenarios